Título Padrão - Oliveira, Claudio (Revista de Letras, 2023)
Translating archaisms can become a challenge for the translator. Keeping or not these terms should be a very well thought out decision, depending on the purpose of the translation. In this paper, we aim to present and comment excerpts from letters written by Mariquita Sánchez, a lady of Buenos Aires society in the nineteenth century, whose translation sought to reproduce the archaic terms used by the missivist. Based on the works of translation criticism and analysis by Costa (2019), supported by the translation theories and strategies explained by theorists in the field of Translation Studies, such as Levý (2012), Berman (1999), Steiner (1975) and Rónai (2012), we reflect that the reproduction of archaisms in translation recreates the atmosphere and the type of language used by speakers of the period in which the texts were written, creating a kind of "illusion" in the reader, as if they were reading the work written in its original language, even if this causes a certain "strangeness".